(untitled) (Web of Teachers: Inderscience Research, 2023)
This article uses examples in Uzbek works to illustrate the role of lion zoosemism in the language, sources of enrichment, theme classification, and its various definitions are proven. The characteristics of zoosemism are listed, as well as the explanation of our lion zoos.